Fatigue Among Youth Workers in Bali 2024 - Kusuma, Made Adhyatma Prawira Natha; Biomi, Agnes Ayu; Negara, Ni Luh Gede Maytadewi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Fatigue is a consequence of work which decreases physical and mental work capacity that indicates the body needs time to rest. Fatigue being one of the factors causing accidents in the workplace. Fatigue can occur in workers of various age ranges, including young workers aged 15-24 years. With the increasing number of young workers who will dominate, it is important to protect young workers from work-related accidents. Objective : To analyze risk factors for fatigue among youth workers including individual, lifestyle, job and psychosocial factors. Research Methods/ Implementation Methods : The study was conducted on young workers of in Bali, involving 298 young workers. The design of this study is a quantitative analytic with cross-sectional study. The instruments used the IFRC for fatigue, PSQI for Sleep Hygiene Index to view sleep hygiene and the questionnaire for further assessment and improvement to prevent ongoing fatigue that is Psychosocial Questionnaire-III. Results : The results showed that most respondents in the category of moderate fatigue (57,72%) with the highest symptoms of fatigue were yawn while working (56.38%). Multivariate analysis using logistic regression tests found that stress variable showed a significant relationship to fatigue with an OR value = 4.28, meaning that stressed workers were 4.28 times more at risk of experiencing fatigue than those without stress. Conclusion/Lesson Learned : In general, fatigue among young workers in workplace in conditions of need is a critical risk of work accidents. There needs to be special attention for young workers fit for the work and fit for the job.